2017
DOI: 10.1002/anie.201706850
|View full text |Cite
|
Sign up to set email alerts
|

Alkynyl Thioethers in Gold‐Catalyzed Annulations To Form Oxazoles

Abstract: Non‐oxidative, regioselective, and convergent access to densely functionalized oxazoles is realized in a functional‐group tolerant manner using alkynyl thioethers. Sulfur‐terminated alkynes provide access to reactivity previously requiring strong donor‐substituted alkynes such as ynamides. Sulfur does not act in an analogous donor fashion in this gold‐catalyzed reaction, thus leading to complementary regioselective outcomes and addressing the limitations of using ynamides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 70 publications
1
51
1
Order By: Relevance
“…[19,20] X-ray diffraction subsequently confirmed the structures of 3aa and 3ga (see the Supporting Information). [21] These first nickel-mediated Kumada-type couplings with 5-thioether oxazoles [22] demonstrate the value of the thioether handle,i nt his case providing substitution patterns which are not directly accessible from the annulation (see 4b in Table 1).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…[19,20] X-ray diffraction subsequently confirmed the structures of 3aa and 3ga (see the Supporting Information). [21] These first nickel-mediated Kumada-type couplings with 5-thioether oxazoles [22] demonstrate the value of the thioether handle,i nt his case providing substitution patterns which are not directly accessible from the annulation (see 4b in Table 1).…”
mentioning
confidence: 96%
“…Thea lkynyl thioether 1j gave 5thioethers 3ja/c as the major isomers,t hus providing 4-alkyl oxazoles.S terically-congested bi(hetero)aryl linkages may also be formed as single regioisomers (3lc). [21]…”
mentioning
confidence: 99%
“…The reactivity‐enhancing effect of a sulfenyl substituent could be explained by sulfur‐gold interactions stabilising the polarised gold keteneiminium contribution B’ to generate a more effective electrophile (Scheme ). Sulfur‐gold interactions could also conceivably help to favour productive gold‐ynamide coordination over unproductive interaction with nitrenoid . Invoking a stabilising dative or hyperconjugative interaction between the gold and sulfur can explain the lower reactivity observed with S ‐phenyl ynamide 18 b over S ‐methyl ynamide 18 a .…”
Section: Figurementioning
confidence: 99%
“…[9] Although alkynes can also generate a-imino gold carbenes by using variousn itrogen-containing nucleophiles, in most cases these a-imino carbenes are transformed into pyrroles and other azacycles through ar apid intramolecular cyclization. [10][11][12] Elaborationo fa-imino gold carbenes for other synthetic applicationsi sl ess explored. Ye and co-workers reported that a-imino gold carbenes could react with alkynes to generate vinyl cations [ Scheme 1,Eq. (2)] [12a] through ap ath distinct from that of a-oxo gold carbenes [Scheme 1, Eq.…”
Section: Introductionmentioning
confidence: 99%